Parenting acceptance and commitment therapy: A randomised controlled trial of an innovative online course for families of children with cerebral palsy - Whittingham, K.; Sheffield, J.; Boyd, Roslyn (BM J Group, 2016)
Introduction Cerebral palsy (CP) impacts on the entire family in a manner that is long-term, complex and multifactorial. In addition, the quality of the parent-child relationship impacts on many and varied child outcomes, making the provision of easily accessible and evidence-based support to parents of children with CP a priority. This paper reports the protocol of a randomised controlled trial of an innovative and translatable online intervention, parenting acceptance and commitment therapy (PACT), for families of children with CP. We predict that participating in the PACT programme will be associated with improvements in the parent-child relationship, in child functioning and in adjustment and quality of life for both parent and child. Methods and analysis We aim to recruit 66 parents of children (2-10 years old) diagnosed with CP to this study. Families will be randomly assigned to two groups: wait-list control and PACT. PACT is a parenting intervention grounded in acceptance and commitment therapy (ACT) and developed into an online course PARENT101 Parenting with Purpose' using the edX platform. All participants will be offered PACT before completion of the study. Assessments will take place at baseline, following completion of PACT and at 6-month follow-up (retention) and will focus on the parent-child relationship, parent and child adjustment and parent and child quality of life. Analysis will follow standard methods for randomised controlled trials using general linear models, specifically analysis of variance or analysis of covariance. Ethics and dissemination Ethics approvals have been obtained through the Children's Health Queensland Hospital and Health Service Human Research Ethics Committee (HREC/15/QRCH/115) and The University of Queensland (2015001743). If efficacy is demonstrated, then the PARENT101 course has the potential to be disseminated widely in an accessible manner and at minimal cost. Further, the PACT framework may provide a blueprint for similar online courses with parents in a full range of contexts.